Super sleuth - O'Connor, Jane.; Preiss-Glasser, Robin (New York, N.Y. : Harper, 2012)
"In her chapter book debut, Nancy Clancy must find the culprit when a prized possession goes missing at school"-- Provided by publisher.
007-010.
Accelerated Reader AR
Keywords: Lost articles -- Juvenile fiction; Schools -- Juvenile fiction; Vocabulary -- Juvenile fiction; Mystery and detective stories; Lost and found possessions -- Fiction; Schools -- Fiction; Vocabulary -- Fiction